Performance of CIAE Animal Drawn Puddler in Kashmir Valley - Dixit, Jagvir (Journal of Agricultural Engineering, 2006)
A field experiment was conducted to study the performance of CIAE animal drawn puddler in respect of puddling quality and economical aspect under wet silty loam soil conditions. Puddling quality was judged on the basis of puddling index, bulk density, percolation loss and crop yield. The performance of animal drawn puddler in terms of puddling index and percolation loss was found better as compared to puddling by rotary tiller and conventional method of puddling. The field capacity and field efficiency were observed 0.10 ha/h and 71.42 percent in case of animal drawn puddler, which were 87 and 23 percent higher than traditional method of puddling. The cost of operation under animal drawn puddler, rotary tiller and local plough was calculated to be Rs 182, 1105 and 1188 per ha, respectively.